A Theoretical Study of Correlated Electron in the Frustrated Hubbard Model: Summary Report: Sabbatical Leave Spring 2010 - Enjalran, Matthew (2010)
This sabbatical leave was devoted to conducting theoretical, computational studies of correlated electrons with frustrated interactions and focus on the Hubbard model on the two-dimensional triangular and kagome lattices. Secondly, two Quantum Monte Carlo (QMC) methods were developed and applied to the models of the constrained path/phase QMC, and the determinant QMC methods.
Keywords: dept.phy; faculty_collection; sabbatical_report

An inquiry-based course in nano-photonics - Broadbridge, C.; Calvert, J.; Donnelly, J.; Garofano, J.; Massa, N. (Proc SPIE Int Soc Opt Eng, 2010)
We developed a curriculum to introduce nanotechnology and photonics concepts to community college students enrolled in a program designed to attract and retain students in technology associate degree programs. Working with the Center for Research on Interface Structures and Phenomena, an NSF Materials Research Science and Engineering Center, and the PHOTON projects, funded by the Advanced Technological Education program of NSF, we developed hands-on, inquiry-based activities to address the course goals: improve critical thinking, introduce science and technology concepts common to technology programs and provide opportunity to practice math skills in context. © 2010 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc SPIE Int Soc Opt Eng
Keywords: Advanced Technological Education; Associate degree; Community college; Critical thinking; Curricula; Education; Inquiry; Interface structures; Materials research; Math skills; Nano-photonics; Nanotechnology; Photonics; Science and Technology; Science and engineering; Students; Technology programs; dept.phy

Interface-induced polarization and inhibition of ferroelectricity in epitaxial SrTiO3/Si - Kolpak, A.M.; Walker, F.J.; Reiner, J.W.; Segal, Y.; Su, D.; Sawicki, M.S.; Broadbridge, C.C.; Zhang, Z.; Zhu, Y.; Ahn, C.H.; Ismail-Beigi, S. (Physical Review Letters, 2010)
We use SrTiO3/Si as a model system to elucidate the effect of the interface on ferroelectric behavior in epitaxial oxide films on silicon. Using both first-principles computations and synchrotron x-ray diffraction measurements, we show that structurally imposed boundary conditions at the interface stabilize a fixed (pinned) polarization in the film but inhibit ferroelectric switching. We demonstrate that the interface chemistry responsible for these phenomena is general to epitaxial silicon-oxide interfaces, impacting on the design of silicon-based functional oxide devices. © 2010 The American Physical Society.
64 citations (Crossref) [2023-10-31]
Keywords: Epitaxial films; Epitaxial silicon; Ferroelectric behavior; Ferroelectric films; Ferroelectric switching; Ferroelectricity; First-principles; Functional oxides; Induced polarization; Interface chemistry; Mathematical models; Model system; Oxide films; Polarization; Semiconducting silicon compounds; Silicon oxides; Silicon-based; SrTiO; Strontium alloys; Synchrotron x ray diffraction; X ray diffraction; dept.phy

The atomic structure and polarization of strained SrTiO3/Si - Kumah, Divine; Reiner, James W.; Segal, Y.; Kolpak, Alexie M.; Zhang, Zhizhi; Su, Dong; Zhu, Yimei; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H.; Walker, Fred (Applied Physics Letters, 2010)
For thin film devices based on coupling ferroelectric polarization to charge carriers in semiconductors, the role of the interface is critical. To elucidate this role, we use synchrotron x-ray diffraction to determine the interface structure of epitaxial SrTiO3 grown on the (001) surface of Si. The average displacement of the O octahedral sublattice relative to the Sr sublattice determines the film polarization and is measured to be about 0.05 nm toward the Si, with Ti off-center displacements 0.009 nm away from the substrate. Measurements of films with different boundary conditions on the top of the SrTiO3 show that the polarization at the SrTiO3 /Si interface is dominated by oxide-Si chemical interactions. © 2010 American Institute of Physics.
25 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: Atomic structure; Chemical interactions; Crystal atomic structure; Different boundary condition; Ferroelectric polarization; Interface structures; Polarization; Semiconducting silicon compounds; Silicon; SrTiO; Strontium alloys; Sub-lattices; Synchrotron x ray diffraction; Thin film devices; X ray diffraction; dept.phy

Kepler observations of three pre-launch exoplanet candidates: discovery of two eclipsing binaries and a new exoplanet - Howell, Steve Bruce; Rowe, Jason F.; Sherry, William; von Braun, Kaspar; Ciardi, David R.; Bryson, Stephen T.; Feldmeier, John J.; Horch, Elliott P.; van Belle, Gerard T. (The Astrophysical Journal, 2010)
Three transiting exoplanet candidate stars were discovered in a ground-based photometric survey prior to the launch of NASA's Kepler mission. Kepler observations of them were obtained during Quarter 1 of the Kepler mission. All three stars are faint by radial velocity follow-up standards, so we have examined these candidates with regard to eliminating false positives and providing high confidence exoplanet selection.We present a first attempt to exclude false positives for this set of faint stars without high-resolution radial velocity analysis. This method of exoplanet confirmation will form a large part of the Kepler mission follow-up for Jupiter-sized exoplanet candidates orbiting faint stars. Using the Kepler light curves and pixel data, as well as medium-resolution reconnaissance spectroscopy and speckle imaging, we find that two of our candidates are binary stars. One consists of a late-F star with an early M companion, while the other is a K0 star plus a late M-dwarf/brown dwarf in a 19 day elliptical orbit. The third candidate (BOKS-1) is an r = 15 G8V star hosting a newly discovered exoplanet with a radius of 1.12 RJupiter in a 3.9 day orbit. © 2010 The American Astronomical Society. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00072 tex.type: [object Object]
Keywords: Binaries: eclipsing; Brown dwarfs; Planetary systems; dept.phy

Visualizing bone porosities using a tabletop scanning electron microscope - Krishnamoorthy, D.; DaPonte, J.; Broadbridge, C. C.; Daniel, D.; Alter, L. (Visual Information Processing XIX, 2010)
Pores are naturally occurring entities in bone. Changes in pore size and number are often associated with diseases such as Osteoporosis and even microgravity during spaceflight. Studying bone perforations may yield great insight into bone's material properties, including bone density and may contribute to identifying therapies to halt or potentially reverse bone loss. Current technologies used in this field include nuclear magnetic resonance, micro-computed tomography and the field emission scanning electron microscope (FE-SEM)^ 2, 5. However, limitations in each method limit further advancement. The objective of this study was to assess the effectiveness of using a new generation of analytical instruments, the TM-1000 tabletop, SEM with back-scatter electron (BSE) detector, to analyze cortical bone porosities. Hind limb unloaded and age-based controlled mouse femurs were extracted and tested in vitro for changes in pores on the periosteal surface. An important advantage of using the tabletop is the simplified sample preparation that excludes extra coatings, dehydration and fixation steps that are otherwise required for conventional SEM. For quantitative data, pores were treated as particles in order to use an analyze particles feature in the NIH ImageJ software. Several image-processing techniques for background smoothing, thresholding and filtering were employed to produce a binary image suitable for particle analysis. It was hypothesized that the unloaded bones would show an increase in pore area, as the lack of mechanical loading would affect bone-remodeling processes taking place in and around pores. Preliminary results suggest only a slight different in frequency but not in size of pores between unloaded and control femurs.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-681-726-544-835, pop00157 tex.type: [object Object]
Keywords: Bone; Computerized tomography; Data processing; Electron microscopes; Electrons; Intracortical; Mammals; Particle analysis; Periosteal; Resonance; Scanning; Scanning electron microscope; Scanning electron microscopy; Threshold; Tomography; dept.phy

Kepler Planet-Detection Mission: Introduction and First Results. - Borucki, William; Koch, David; Basri, Gibor; Batalha, Natalie; Brown, Timothy; Caldwell, Douglas; Caldwell, John; Christensen-Dalsgaard, Jorgen; Cochran, William; DeVore, Edna; Dunham, Edward; Dupree, Andrea; et al. (Science, 2010)
The Kepler mission was designed to determine the frequency of Earth-sized planets in and near the habitable zone of Sun-like stars. The habitable zone is the region where planetary temperatures are suitable for water to exist on a planet's surface. During the first 6 weeks of observations, Kepler monitored 156,000 stars, and five new exoplanets with sizes between 0.37 and 1.6 Jupiter radii and orbital periods from 3.2 to 4.9 days were discovered. The density of the Neptune-sized Kepler-4b is similar to that of Neptune and GJ 436b, even though the irradiation level is 800,000 times higher. Kepler-7b is one of the lowest-density planets (∼0.17 gram per cubic centimeter) yet detected. Kepler-5b, -6b, and -8b confirm the existence of planets with densities lower than those predicted for gas giant planets.
2612 citations (Crossref) [2023-10-31] Place: Copyright (C) 2010 by the American Association for the Advancement of Science
Keywords: Jupiter; article; astronomy; astrophysics; density; dept.phy; gas; irradiation; planetary atmosphere; planetary surface; priority journal; spacecraft; sun; temperature; water

Beta-Test Data On An Assessment Of Textbook Problem Solving Ability: An Argument For Right∕Wrong Grading? - Cummings, Karen; Marx, Jeffrey D.; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 Physics Education Research Conference, 2010)
We have developed an assessment of students' ability to solve standard textbook style problems and are currently engaged in the validation and revision process. The assessment covers the topics of force and motion, conservation of momentum and conservation of energy at a level consistent with most calculus-based, introductory physics courses. This tool is discussed in more detail in an accompanying paper by Marx and Cummings. [1] Here we present preliminary beta-test data collected at four schools during the 2009/2010 academic year. Data include both pre- and post-instruction results for introductory physics courses as well as results for physics majors in later years. In addition, we present evidence that right/wrong grading may well be a perfectly acceptable grading procedure for a course-level assessment of this type. © 2010 American Institute of Physics.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/136-768-475-813-84X, pop00255 tex.number: [object Object]
Keywords: Problem solving in physics; assessment; dept.phy; introductory physics; right/wrong grading

Bridging the length scales between lithographic patterning and self assembly mechanisms in fabrication of semiconductor nanostructure arrays - Hull, Robert; Floro, J A; Gherasimova, M; Graham, J; Gray, J L; Portavoce, A; Ross, Frances M; Thorp, J (Journal of Physics: Conference Series, 2010)
We employ focused ion beam patterning of single crystal Si(100) surfaces to template the assembly of Ge(Si) nanostructure arrays. The evolution and final structures of the templated arrays are determined by combinations of transmission electron, low energy electron microscope, focused ion beam and scanning probe microscopies. It is shown how the positions of individual nanostructures may be controlled to the order of 10 nm. However, to achieve controlled spacings between elements that are in the 10 nm range requires careful matching of the characteristic lengths scales of self assembly mechanisms to the length scales of the external lithographic "forcing functions". © 2010 IOP Publishing Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-366-191-463-372
Keywords: Assembly mechanism; Characteristic length; Electrons; Focused ion beams; Germanium; Ion beams; Lithographic patterning; Low energy electron microscopes; Nanostructure arrays; Nanostructures; Self assembly; Semiconductor nanostructures; Silicon wafers; Single crystal surfaces; Single crystals; Single-crystal Si; Transmission electron; dept.phy

Development of a Survey Instrument to Gauge Students’ Problem-Solving Abilities - Marx, Jeffrey; Cummings, Karen; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 Physics Education Research Conference, 2010)
In this paper we discuss the early stages of development of a survey instrument to assess students' problem-solving abilities in a first-term, undergraduate, calculus-based physics course. Specifically, we present our motivation for the development of such a survey, details of a preliminary version of the survey, and some sample items. © 2010 American Institute of Physics.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-977-856-086-461, pop00163 tex.number: [object Object]
Keywords: Problem-solving; assessment; dept.phy; introductory physics

Comparison of the ability of quantitative parameters to differentiate surface texture of Atomic Force Microscope (AFM) images - Niedzielski, Bethany; Broadbridge, Christine; Daponte, John S; Gherasimova, Maria (Machine Vision Applications, 2010)
The purpose of this study was to compare the ability of several texture analysis parameters to differentiate textured samples from a smooth control on images obtained with an Atomic Force Microscope (AFM). Surface roughness plays a major role in the realm of material science, especially in integrated electronic devices. As these devices become smaller and smaller, new materials with better electrical properties are needed. New materials with smoother surface morphology have been found to have superior electrical properties than their rougher counterparts. Therefore, in many cases surface texture is indicative of the electrical properties that material will have. Physical vapor deposition techniques such as Jet Vapor Deposition and Molecular Beam Epitaxy are being utilized to synthesize these materials as they have been found to create pure and uniform thin layers. For the current study, growth parameters were varied to produce a spectrum of textured samples. The focus of this study was the image processing techniques associated with quantifying surface texture. As a result of the limited sample size, there was no attempt to draw conclusions about specimen processing methods. The samples were imaged using an AFM in tapping mode. In the process of collecting images, it was discovered that roughness data was much better depicted in the microscope's "height" mode as opposed to "equal area" mode. The AFM quantified the surface texture of each image by returning RMS roughness and the first order histogram statistics of mean roughness, standard deviation, skewness, and kurtosis. Color images from the AFM were then processed on an off line computer running NIH ImageJ with an image texture plug in. This plug in produced another set of first order statistics computed from each images' histogram as well as second order statistics computed from each images' cooccurrence matrix. The second order statistics, which were originally proposed by Haralick, include contrast, angular second moment, correlation, inverse difference moment, and entropy. These features were computed in the 0°, 45°, 90°, and 135° directions. The findings of this study propose that the best combination of quantitative texture parameters is standard deviation, 0° inverse difference moment, and 0° entropy, all of which are obtained from the NIH ImageJ texture plug in. © 2010 Copyright SPIE - The International Society for Optical Engineering.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: AFM; Angular second moment; Atomic force microscopes; Atomic force microscopy; Cluster analysis; Co-occurrence-matrix; Color images; Computer vision; Crystal growth; Deposition; Electric properties; Electrical property; First order; First-order statistics; Graphic methods; Growth parameters; Histogram statistics; Image processing technique; Image texture; Imaging systems; Integrated electronics; Inverse differences; Jet vapor depositions; Material science; Materials; Mean roughness; Microscopes; Molecular beam epitaxy; Molecular beams; New material; Photoresists; Physical vapor deposition; Plug-ins; Processing; Processing method; Quantitative parameters; RMS roughness; Regression analysis; Sample sizes; Second order statistics; Smooth control; Standard deviation; Statistics; Surface morphology; Surface roughness; Surface textures; Surfaces; Tapping modes; Texture analysis; Textures; Thin layers; dept.phy

Valence electron energy-loss spectroscopy of ultrathin SrTiO3 films grown on silicon (100) single crystal - Su, Dong; Yang, Bo; Jiang, Nan; Sawicki, Monica; Broadbridge, Christine; Couillard, M; Reiner, James W; Walker, Fred; Ahn, C H; Zhu, Yimei (Applied Physics Letters, 2010)
Valence electron energy-loss spectroscopy is used to investigate the plasmon excitations of ultrathin SrTiO3 sandwiched between amorphous Si and crystalline Si. Two plasmon excitations were observed, one at 15.8 eV and the other at 28.7 eV. Our calculations, based on dielectric-function theory, suggest that the former peak originates from the coupling of the Si layers and is related to the geometry of the structure, and the latter peak results from the SrTiO3 bulk plasmon after a redshift. Our findings demonstrate the value of valence electron energy-loss spectroscopy in detecting a local change in the effective electron mass. © 2010 American Institute of Physics.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-562-101-735-184 tex.type: [object Object]
Keywords: Amorphous Si; Amorphous silicon; Crystalline Si; Dissociation; Electron energy loss spectroscopy; Electron scattering; Electrons; Function theory; Plasmon excitations; Plasmons; Red shift; Si layer; Silicon (100); Silicon wafers; Single crystals; SrTiO; Strontium alloys; Ultra-thin; Valence electron energy-loss spectroscopies; dept.phy

Determination of electronic structure of Oxide–Oxide interfaces by photoemission spectroscopy - Wang, Huiqiong; Altman, Eric I; Broadbridge, Christine; Zhu, Yimei; Henrich, Victor E (Advanced Materials, 2010)
A method has been developed to use the finite escape depth of the photoelectrons emitted in ultraviolet photoemission spectroscopy (UPS) to determine the electronic density-of-states at the interface between two dissimilar metal oxides. Ultrathin films of one oxide are grown heteroepitaxially, one monolayer at a time, on a single-crystal substrate of the other oxide, and UPS spectra are taken after each complete monolayer. By comparing experimental UPS spectra with calculated spectra based on specific models of the interfacial structure, the interfacial density-of-states can be extracted. The two oxide systems studied here are NiO-Fe 3O 4 and CoO-Fe 3O 4. The former system is found to have an atomically abrupt interface, with no significant density of interface states. For CoO, however, an interfacial electronic spectrum, different from that of either the substrate or the overlayer, is found. The spatial extent and possible origin of those interfacial states is discussed. © 2010 WILEY-VCH Verlag GmbH &. Co. KGaA, Weinheim.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-294-835-347-179 tex.type: [object Object]
Keywords: Cobalt; Cobalt compounds; Density of interface state; Dissimilar metals; Electron energy levels; Electronic density; Electronic spectrum; Electronic structure; Emission spectroscopy; Escape depth; Ferumoxytol; Interfacial density; Interfacial state; Interfacial structures; Luminescence of organic solids; Models; Molecular; Monolayers; Nickel; Oxide films; Oxide systems; Oxide-oxide interfaces; Oxides; Photoelectron Spectroscopy; Photoelectron spectroscopy; Photoemission; Photoemission spectroscopy; Single-crystal substrates; Smelting; Spatial extent; UPS spectra; Ultrathin films; Ultraviolet photoemission spectroscopy; X ray photoelectron spectroscopy; article; chemical structure; chemistry; cobalt; cobalt oxide; dept.phy; ferumoxytol; nickel; nickel monoxide; oxide